2019
DOI: 10.1002/dvdy.135
|View full text |Cite
|
Sign up to set email alerts
|

FGF2/EGF contributes to brain neuroepithelial precursor proliferation and neurogenesis in rat embryos: the involvement of embryonic cerebrospinal fluid

Abstract: BackgroundAt the earliest stages of brain development, the neuroepithelium works as an interdependent functional entity together with cerebrospinal fluid, which plays a key regulatory role in neuroepithelial cell survival, replication and neurogenesis; however, the underlying mechanism remains unknown in mammals.ResultsWe show the presence of fibroblast growth factor 2 (FGF2) and epidermal growth factor (EGF), in 13.5‐day rat embryo cerebrospinal fluid (eCSF). Immunohistochemical detection of FGF2 expression l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 55 publications
0
12
0
Order By: Relevance
“…Upon neural tube closure in mammals, the captured amniotic fluid becomes the nascent CSF. In the ensuing period, preceding formation of the CP, it has been shown that CSF composition correlates to large extent with proteomic changes observed in the developing neuroepithelium [14,15], which displays barrier-like properties [16], enabling regulated release of growth factors and particles from neuroepithelium into the CSF [17,18]. Interestingly, the ability of neuroepithelium to tightly control CSF composition in early brain development exhibits interspecies differences, indicating existence of distinct requirements for CSF regulation depending on the complexity of the developing CNS [19,20].…”
Section: Csf-an Intrinsic Component Of Cns Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Upon neural tube closure in mammals, the captured amniotic fluid becomes the nascent CSF. In the ensuing period, preceding formation of the CP, it has been shown that CSF composition correlates to large extent with proteomic changes observed in the developing neuroepithelium [14,15], which displays barrier-like properties [16], enabling regulated release of growth factors and particles from neuroepithelium into the CSF [17,18]. Interestingly, the ability of neuroepithelium to tightly control CSF composition in early brain development exhibits interspecies differences, indicating existence of distinct requirements for CSF regulation depending on the complexity of the developing CNS [19,20].…”
Section: Csf-an Intrinsic Component Of Cns Environmentmentioning
confidence: 99%
“…Neuroepithelium consisting of neuronal progenitors, which segregate to the ventricular zone upon neural tube closure and concomitant ventricular system formation, represent the chief source of cells that will give rise to the entire CNS [169]. Ample evidence collected over the last two decades has clearly established CSF as a crucial signalling component underpinning the key aspects of neuroepithelial behaviour [5,17,170]. Signalling factors such as Semaphorin-3B, released by the embryonic CP were shown to affect orientation of the mitotic spindle and apicobasal polarity, thus controlling division of neural progenitors [23].…”
Section: The Target Brain Regions Of Cp-csf Signallingmentioning
confidence: 99%
“…Neurogenesis, together with gliogenesis, largely depends on molecular and genetic inputs such as growth factors and cellular signaling pathways, creating a microenvironment, or niche, for NS/PCs. Moreover, these processes are also modulated during pathological states (O'Keeffe et al, 2009;Bowman et al, 2013;Lamus et al, 2020). The role of the canonical Wnt signaling pathway in the brain development has been well established (Chenn and Walsh, 2002;Machon et al, 2003Machon et al, , 2007Kalani et al, 2008;Borday et al, 2018;Chodelkova et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, all cellular processes are largely dependent on intrinsic and extrinsic molecular signals, such as growth factors or various components of cellular signaling pathways. On top of that, it is important to realize that these molecular inputs regulate cellular processes not only in health, but also during the pathological states of the CNS [ 125 , 153 ]. There are several cellular signaling pathways that may represent such “crossroads”, connecting brain ischemia and AD; recent research has indicated candidates such as Notch, signal transducer and activator of transcription 3 (Stat3), or Wnt signaling.…”
Section: Common Features Of Ischemic Brain Injury and Alzheimer’s Diseasementioning
confidence: 99%